Pengaruh Profitabilitas Terhadap Pengeluaran Zakat Pada Bank Umum Syariah Di Indonesia Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Irman Firmansyah; Aam S. Rusydiana (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2013)
Tithe is duty that must be taked to follow Islamic religion belongs tithe companies. Therefore that Islamic bank must takes tithe so that as according to guidance alquran.This research to analyze influence of profitability to tithe expenditure in Islamic Bank in Indonesia which is moderated by size of company. Profitability is measured by ROA and size of company is measured by total asset. This Research is empirical study at Islamic Bank in Indonesia in 4 periods of observation in 2009-2012. Method applied in this research is analytical quantitative method with empirical study approach. Data collecting technique by through secondary data that is data obtained from website, literature and the bibliography. Analyzer applied is Moderated Regression Analysis (MRA). The result shows that company size have moderated influence profitability to tithe expenditure at Islamic Bank.